2022
DOI: 10.1227/neu.0000000000002108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fusion versus Nonunion After 4-Level and 5-Level Anterior Cervical Diskectomy and Fusion With Anterior Plate Fixation

Abstract: BACKGROUND:Nonunion remains a concern in multilevel anterior cervical discectomy and fusion (ACDF), yet there are limited data on nonunion after 4 to 5-level ACDF. In fact, the largest series on 4-level or 5-level ACDF focused specifically on the swallowing outcomes.OBJECTIVE:To assess nonunion after 4 to 5-level ACDF.METHODS:Forty-one patients treated with 4 to 5-level ACDF with minimum of 12-month radiographic follow-up were retrospectively reviewed. Nonunion was found in 25 patients (61%) and 42 levels (25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…16 More recent studies by Wewel et al and Bakare et al report similarly high rates of pseudarthrosis at 56% (16 patients with 4-level ACDF) and 61% (45 patients with 4-or 5-level ACDF), respectively. 7,17 Despite less than half of these patients achieving fusion at all of the operative levels, both studies report the rate of fusion per level to be much higher-at 80% and 75%-which parallels the findings in our cohort. 7,17 A majority of cases with nonunion involved only a single level, which was most often at the caudal end of the construct.…”
Section: Discussionsupporting
confidence: 84%
“…16 More recent studies by Wewel et al and Bakare et al report similarly high rates of pseudarthrosis at 56% (16 patients with 4-level ACDF) and 61% (45 patients with 4-or 5-level ACDF), respectively. 7,17 Despite less than half of these patients achieving fusion at all of the operative levels, both studies report the rate of fusion per level to be much higher-at 80% and 75%-which parallels the findings in our cohort. 7,17 A majority of cases with nonunion involved only a single level, which was most often at the caudal end of the construct.…”
Section: Discussionsupporting
confidence: 84%
“…didates for CDA. [45][46][47] Due to arthrodesis-related consequences, 22,39,[48][49][50][51] multilevel CDA is particularly appealing for young patients with multilevel cervical spondylotic myelopathy caused by disc-related problems or congenital stenosis. Chang et al 1 reported a retrospective series of 37 patients younger than 50 years with cervical myelopathy who were treated with either hybrid CDA-ACDF (2-level CDA plus 1-level ACDF, 20 patients) or 3-level ACDF (17 patients).…”
Section: Figmentioning
confidence: 99%
“…20,21 Even with the most advanced instrumentation and biologics, multilevel ACDF is inevitably plagued-at least for some patients-with pseudarthrosis, loss of neck motion, and increased risk of ASD. 22,23 These issues are likely to be more prominent as the constructs get longer. Thus, CDA has emerged as an ideal alternative in these clinical scenarios, with the benefit of obviating fusion and preserving motion to improve the postoperative quality of life in patients with multilevel disc pathology.…”
mentioning
confidence: 99%
“…With the increasing prevalence of multilevel cervical degenerative disease, ACDF remains the more common treatment approach once a patient has been directed toward surgical management. There are significant complications with ACDF as the length of the fusion construct increases, including a higher rate of pseudoarthrosis and ASD, as well as a greater degree of motion loss 6–8 . Given that these issues are more prominent with longer constructs, there has been a justifiable interest in exploring CDA as a potential alternative.…”
mentioning
confidence: 99%